HAK CUTI SUAMI: SUDAHKAH SEJALAN DENGAN PRINSIP MASLAHAH DALAM SIYASAH DUSTURIYAH? - Safwatul Muna; Ihdi Karim Makinara; Husni A. Jalil (Journal of Indonesian Comparative of Syari'ah Law, 2025)
Paternity leave for husbands accompanying their wives after childbirth is a policy that demonstrates progress in family protection and the strengthening of the husband's role in childcare. This article aims to examine the compatibility between the right to paternity leave as stipulated in Law No. 4 of 2024 on the Welfare of Mothers and Children in the First Thousand Days of Life with the principle of maslahah within the framework of Siyasah Dusturiyah. This study employs a normative legal method through a statutory approach and a conceptual approach. The analysis focuses on legal norms and doctrines in Islamic law, particularly the principle of maslahah and Siyasah Dusturiyah. The findings indicate that the policy on the husband's right to leave meets the elements of maslahah mursalah because it provides tangible benefits, does not contradict the text, and encompasses the public interest. This policy also represents the actualization of maqāṣid al-syarī‘ah in protecting life and offspring. Thus, the husband's leave entitlement is an implementation of the values of justice and maslahah in the national legal system that is in line with the principles of Islamic law.